Height‐Latitude Patterns of Interannual Climate Variability in the Upper Mesosphere and Lower Thermosphere During Spring and Autumn Months - Liang Zhang; Zhongfang Liu; Brian Tinsley (Geophysical Research Letters)
Abstract The upper mesosphere and lower thermosphere (UMLT) remains the least explored and least understood atmospheric region. Using Microwave Limb Sounder and Sounding of the Atmosphere using Broadband Emission Radiometry observations, we demonstrate the interannual variability of UMLT climate during spring and autumn months is controlled by bottom‐up processes: tropical upwelling drives the transport of H2O, increasing atomic hydrogen (H) which destroys O3; the interannual variability of atomic oxygen (O) coincides with that of O3 due to the ozone photochemical equilibrium; radiative and chemical heating of Ox (O and O3) influences temperatures above 90 km (T90). This “upwelling—H2O—Ox—T90” link propagates upward and poleward via dynamic transports. Temperatures at ∼20°S/N near 80 km (T80), dominated by adiabatic cooling, serve as an indicator of tropical upwelling. Notably, mid‐to‐high‐latitude T90 is positively correlated with low‐latitude T80 in both hemispheres, and the interannual variability of H2O, O3, and T90 exhibits remarkable interhemispheric symmetry. These bottom‐up processes may affect solar signal extractions.